Characterization of Natural Cellulosic Fibers from Stem of Symphirema Involucratum Plant - Juvvi Siva Naga Raju; Melvin Victor Depoures; JABIHULLA Shariff; SUDHIR Chakravarthy (Journal of Natural Fibers, 2022)
This study investigated the physical, chemical, thermal, morphological, and XRD analysis of Symphirema involucratum stem fiber to establish its suitability in composite reinforcements. The investigation on chemical components proved that the fiber possesses a good amount of cellulose content (57.32%) with low lignin (13.85%), hemicellulose (12.47%), wax (0.56%), moisture (9.11%), and ash (9.05%) contents. The fiber showed a density of 1389 kg/m3, a diameter of 542.26 ± 10.32 µm, and a crystallinity index of 28.22%. Higher maximum degradation temperature (350°C) with a kinetic activation energy of 74.88 kJ/mol obtained by thermogravimetric analysis. Nuclear magnetic resonance spectra confirmed the presence of high cellulose content at the intensities of the C-2, C-3, and C-5 lines. The microscopic examination of the SISF through a scanning electron microscope and atomic force microscopy revealed that the fiber possesses quite a high coarse fracture surface with pores. The properties of the SISF propose its suitability toward use as an alternative to man-made synthetic fibers.